Minority Groups and Success in Election Primaries - Gil S. Epstein; Odelia Heizler (Global Labor Organization (GLO), 2018)
In this paper, we focus on the effect of belonging to one or more minority groups on the probability of success in primary elections. Using a unique dataset of candidates in Israeli primaries, we find that while being a new immigrant, a woman or a Muslim decreases the chances of electoral success, candidates who belong to two minority groups have an advantage in the race. In some cases of candidates belonging to two minority groups, their chances of success are not only higher than for a candidate from one minority group, but also than for a candidate from the majority.
Keywords: 330; primary elections; success; minority groups; majority groups